The Role of Establishing a Multidisciplinary Team for Idiopathic Granulomatous Mastitis in Improving Patient Outcomes and Spreading Awareness about Recent Disease Trends. (27th January 2020) - Yaghan, Rami J.; Ayoub, Nehad M.; Hamouri, Shadi; Al-Mohtaseb, Alia; Gharaibeh, Maha; Yaghan, Lamees; Al-Dari, Mahmoud; Al-Kaff, Hiba; Al-Zoubi, Nabil A.
Abstract : Background . Iidiopathic granulomatous mastitis (IGM) is stereotypically described as a mysterious entity that mimics breast carcinoma imposing management challenges. In 2002, we established a multidisciplinary team to treat patients with IGM. This study aimed to evaluate the role of this team in improving patient outcomes. Also, a review of literature is provided to highlight recent disease trends. Patients and Methods . Pertinent data for 44 patients treated for IGM from 2002 to 2018 were analyzed and compared to data prior to 2002. Results . Mean age at diagnosis was 37.9 years ± 6.4. The diagnosis of IGM was confirmed by True-cut biopsy (TCB), Frozen section (FS), and surgical biopsy in 70.5%, 25%, and 4.5% of patients, respectively. FS was used to assess the resection margins in three patients. Suspicion for malignancy was raised in one out of 39 ultrasound reports, and one out of 20 mammography reports. Wide local excision was the main treatment modality (95.5%). 19 patients (43.2%) received corticosteroids. Prior to 2002, IGM was only recognized after surgical resection with a 71% initial false impression of carcinoma. After 2002, the initial false clinical impression of carcinoma dropped to 29.5%. Recurrence rate was 31.82%. Younger age at diagnosis was significantly associated with recurrence ( χ 2  = 5.598; p = 0.018 ). Chi-square analysis showed no significant association between BMI and recurrence ( χ 2  = 0.776; p = 0.678 ). Conclusion . The establishment of a multidisciplinary team for IGM was associated with a reduced erroneous impression of breast cancer, and a reduced false positive radiological diagnosis of breast carcinoma. FS was a useful confirmatory procedure. Our series included the first case of a diffuse papular rash as a systemic manifestation of IGM. Recent literature indicates that IGM is changing its face. IGM is being reported in all age groups, and even in males. The clinical manifestations have markedly expanded. Diagnosis by TCB has replaced blind surgical excision. More data regarding predictors of recurrence is accumulating.